2015
DOI: 10.1093/schbul/sbv105
|View full text |Cite
|
Sign up to set email alerts
|

AMIGO-Kv2.1 Potassium Channel Complex is Associated With Schizophrenia-Related Phenotypes

Abstract: The enormous variability in electrical properties of neurons is largely affected by a multitude of potassium channel subunits. Kv2.1 is a widely expressed voltage-dependent potassium channel and an important regulator of neuronal excitability. The Kv2.1 auxiliary subunit AMIGO constitutes an integral part of the Kv2.1 channel complex in brain and regulates the activity of the channel. AMIGO and Kv2.1 localize to the distinct somatodendritic clusters at the neuronal plasma membrane. Here we have created and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 61 publications
2
29
0
Order By: Relevance
“…Knockdown of AMIGO-1 expression in developing zebrafish impairs the formation of fasciculated fiber tracts and disturbs the development of dopaminergic circuits (Zhao et al, 2014 ). However there are no gross anatomical abnormalities in the brains of constitutive global AMIGO-1 KO mice (Peltola et al, 2016 ), or, as shown here, in Kv2 dKO mice, which also have greatly reduced levels of AMIGO-1 expression, particularly in the neuronal PM. Future studies investigating the expression and localization of AMIGO-1 during development in WT and Kv2 KO mice may shed light on whether AMIGO-1 plays a distinct role as a cell adhesion protein promoting axon growth and fasciculation (Kuja-Panula et al, 2003 ) and/or dendritic outgrowth (Chen et al, 2012 ) during early mouse development, and how this role is impacted by Kv2 α subunits.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Knockdown of AMIGO-1 expression in developing zebrafish impairs the formation of fasciculated fiber tracts and disturbs the development of dopaminergic circuits (Zhao et al, 2014 ). However there are no gross anatomical abnormalities in the brains of constitutive global AMIGO-1 KO mice (Peltola et al, 2016 ), or, as shown here, in Kv2 dKO mice, which also have greatly reduced levels of AMIGO-1 expression, particularly in the neuronal PM. Future studies investigating the expression and localization of AMIGO-1 during development in WT and Kv2 KO mice may shed light on whether AMIGO-1 plays a distinct role as a cell adhesion protein promoting axon growth and fasciculation (Kuja-Panula et al, 2003 ) and/or dendritic outgrowth (Chen et al, 2012 ) during early mouse development, and how this role is impacted by Kv2 α subunits.…”
Section: Discussionsupporting
confidence: 61%
“…The brains were removed and cryoprotected for 24 h in 10% sucrose 0.1 M PB, and then for 24–48 h in 30% sucrose in 0.1 M PB. Perfusion-fixed brains from age- and sex-matched WT and AMIGO-1 KO mice (Peltola et al, 2016 ) were prepared in strict accordance with the Guide for the Care and Use of Laboratory Animals of the U.S. National Institutes of Health (NIH), and were approved by the Helsinki University Institutional Animal Care and Use Committee. Perfusion-fixed and cryoprotected ferret brains were gifts from the laboratory of our late colleague Dr. Barbara Chapman.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found schizophrenia-like behavioural and pharmacological abnormalities in AMIGO knock-out mice. Based on these findings and in collaboration with the psychiatrist, Tiina Paunio, AMIGO loss-of-function variants were discovered as risk factors of schizophrenia (Peltola et al, 2016).…”
Section: Psychiatry: From Pet Imaging To Genetics and Translationmentioning
confidence: 99%
“…The Kv2.1 delayed rectifier channel is a Kv channel isoform highly expressed in the AIS (Sarmiere et al, 2008;King et al, 2014), and it has recently been shown that de novo mutations in the KCNB1 gene encoding Kv2.1 are associated with congenital encephalopathic epilepsy (Torkamani et al, 2014;Saitsu et al, 2015;Thiffault et al, 2015). Furthermore, a recent study implied that certain polymorphisms KCNB1 comprise a major risk factor of schizophrenia (Peltola et al, 2016). Kv2.1 is unique in that it is expressed in both the somatodendritic membrane (Trimmer, 1991;Scannevin et al, 1996;Du et al, 1998) and in the AIS (Sarmiere et al, 2008;King et al, 2014), contrasting the general tendency of voltage-gated ion channels to exhibit specific localization in either the somatodendritic or axonal membranes (Jensen et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%